The neutrophil-to-lymphocyte ratio: A potential predictor of poor prognosis in adult patients with trauma and traumatic brain injury - Xu, Jinghong; Li, Shuhe; Lui, Ka Yin; Song, Xiaodong; Hu, Xiaoguang; Cao, Lu; Zhu, Yanping; Huang, Fa; Lin, Xiaobin; Cai, Changjie (Frontiers in Surgery, 2022)
Purpose: This study aimed to determine the prognostic impact of the neutrophil-lymphocyte ratio (NLR) in critically ill trauma patients. Methods: This retrospective study involved adult trauma patients from 335 ICUs at 208 hospitals stored in the eICU database. The primary outcome was ICU mortality. The length of ICU and hospital stay were calculated as the secondary outcomes. Multivariable logistic regression model was used to identify independent predictors of mortality. To identify the effect of NLR on survival, 15-day survival curve was used. Results: A total of 3865 eligible subjects were enrolled. Univariate analysis showed that patients in the group with higher NLR were more likely to receive aggressive methods of care delivery: mechanical ventilation, vasopressor and antibiotics (P＜0.001 for all). The ICU, in-hospital and 15-day mortality of the four groups increased in turn (P＜0.001 for all). The multivariable logistic Cox regression model indicated that higher NLR was an independent risk factor of ICU mortality in trauma patients. ROC analysis showed NLR had better predictive capacity on mortality of patients with TBI than those with trauma (AUC 0.725 vs 0.681). NLR > 7.44 was an independent risk factor of ICU death in patients with TBI (OR: 1.837, 95% CI: 1.045-3.229) and TBI victims whose NLR > 7.44 had 15-day survival disadvantage (P = 0.005). Conclusion: High NLR is associated with poor prognosis of trauma patients, even worse in patients with TBI. NLR > 7.44 is an independent risk factor of death in patients with TBI.